SISTEM INFORMASI PENGAJUAN DOSEN PEMBIMBING BERBASIS WEBSITE PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Badiuzzaman Abdur Rohman (2023)
UPN "Veteran" Jakarta is a university that has seven scientific fields offered, one of them is a computer science fields or called the Faculty of Computer Science. In the scope of the Faculty of Computer Science, the process of applying for a supervisor is still not fully computerized and integrated, where if students want to apply for a supervisor, they still use google form media and there is no system that can serve the submission of supervisor for PKM, MBKM (Intern), Internship, and Thesis. In addition, information regarding the list of lecturers who can be used as supervisors along with their areas of expertise and the maximum quota limit for each lecturer has not been properly published. Based on these problems, as the basis for this research, the proposed solution is to build a supervisor submission information system in the Faculty of Computer Science, UPN "Veteran" Jakarta. The information system will be developed by adopting the waterfall model and using the PHP (Hypertext Preprocessor) version 8.1 programming language and MySQL as the database server. This system includes the process of submitting supervisors and registration of lecturer guidance, approval, or rejection of requests for guidance, validation of guidance, management of supervisor data and program data. The development of this information system is expected to facilitate students in applying for a supervisor to be better and easier also to improve the ease of service for submitting supervisors in the Faculty of Computer Science, UPN "Veteran" Jakarta.